Why Are SGLT2 Inhibitors Nephroprotective? Mechanisms of Action And Possible Benefits A Review - Santos-Alonso, Carlos; Díaz-García, Elena; Costero, Olga; Maldonado-Martín, María; Selgas , Rafael (Journal of Medical Biomedical and Applied Sciences, 2020)
Recent researches have demonstrated that SGLT2i (Sodium-Glucose Linked Transporter 2 inhibitors) play a role in preventing the development and progression of chronic kidney disease (CKD). However, these studies have not to look into the mechanisms that justify this progress. In this document, we will approach the physiologic causes of the kidney response to SGLT2i treatment. SGLT2i were firstly designed as physiologic antidiabetic drugs due to its glucose anti-absorptive action in kidneys. Nevertheless, the effect on glucose levels has proved to be modest, so other different ways have to be involved in their renal benefits. After the commercialization of these drugs, their hypouricemic action, antihypertensive effects, and weight loss have been noticed. Although those actions are positive for the kidney, they are mild and hardly could induce a reduction of proteinuria and a kidney function stabilization effect. Other actions such as anti-inflammatory and metabolic could have more importance in the role of SGLT2i. SGLT2i have been shown to reduce hypoxia and fibrosis in the kidney by changing energetic balance and by reducing inflammatory activity. These two mechanisms are closely related to the settlement and progression of CKD. In addition, SGLT2i reduce proteinuria, which is probably the leading contribution of these drugs for renal function stabilization, due in part to its hemodynamic action by reducing intraglomerular pressure (tubule glomerular balance). In conclusion, SGLT2i kidney benefits could hardly be explained by a single effect. In fact, SGLT2i trigger several effects, that taken together explain the kidney improvements that have been described.